Oris homeopatije v Sloveniji od začetka 19. stoletja do danes - Židov, Nena (Etnolog. Nova vrsta (Ljubljana), 1996)
The article discusess the presence of Hehnemann's homeopathy in Slovenia from the early 19th century to the present day. Despite the fact that homeopathy was banned in 1819 some physicians and laymen continued to practice it and homeopathy survived until the end of the Second World War. In the recent years the expansion of alternative medicine has revived the interest in homeopathy.
Keywords: Židov, Nena, 1957-; Slovenia; Slovenija; ethnology; etnologija; alternativna medicina; homeopatija; zgodovinski pregledi; naravno zdravljenje; medicina; medicine